1992
DOI: 10.1111/j.1600-0447.1992.tb03255.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of long‐term lithium treatment on the mortality of patients with manic‐depressive and schizoaffective illness*

Abstract: Clinical research centers in Aarhus, Berlin, Hamilton and Vienna collected mortality data for 827 manic-depressive and schizoaffective patients given lithium treatment for more than 6 months. The average duration of the treatment was 81 months and the total time on lithium 5600 patient-years. For each patient, the mortality risk was calculated by entering the appropriate national life tables for the general population. The number of observed deaths was 44; the number of expected deaths was 49.7. The standardiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
2
4

Year Published

1994
1994
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(74 citation statements)
references
References 13 publications
3
64
2
4
Order By: Relevance
“…Several studies on the mortality of affective disorders during lithium long-term treatment by Coppen et al [23] and by the International Group for the Study of LithiumTreated Patients (IGSLI) [14,24] demonstrated that the SMR of patients with affective disorders during adequate lithium medication is normalized down to the level of the general population 1 . Coppen [25] reviewed the studies existing in the mid-nineties on the suicide rates in patients on versus off lithium and concluded that adequate lithium medication reduces the suicide-related mortality by 82%.…”
Section: Early Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies on the mortality of affective disorders during lithium long-term treatment by Coppen et al [23] and by the International Group for the Study of LithiumTreated Patients (IGSLI) [14,24] demonstrated that the SMR of patients with affective disorders during adequate lithium medication is normalized down to the level of the general population 1 . Coppen [25] reviewed the studies existing in the mid-nineties on the suicide rates in patients on versus off lithium and concluded that adequate lithium medication reduces the suicide-related mortality by 82%.…”
Section: Early Studiesmentioning
confidence: 99%
“…In the IGSLI main study, well-documented data on the course of illness of 827 patients with affective disorders from lithium clinics in Austria, Canada, Denmark, and Germany, who had been treated with lithium for at least 6 months, were evaluated [14,24] . Fifty-five percent of the patients were bipolar, 25% unipolar, 2% unipolar-manic, 16% schizoaffective, and 2% had other diagnoses.…”
Section: The Igsli Studiesmentioning
confidence: 99%
“…There now exists a large body of data compatible with the conclusions that long-term lithium treatment markedly reduces mortality and suicidal behavior and that the mortality of affective disorders is diminished to a level indistinguishable from that of the general population (e.g., Müller-Oerlinghausen et al 1992, Coppen et al 1992. The antisuicidal effect is also supported by findings from a comparative, long-term study of lithium and carbamazepine, in which only lithium-treated patients remained completely free of suicides (Greil et al 1997).…”
Section: Reduction Of Suicidal Behavior and Mortalitymentioning
confidence: 83%
“…Over the years, however, the initially narrow scope of lithium's caliber in affective disorders has quickly ex-panded, adding to its well-established antimanic and prophylactic benefits antiaggressive effects (particularly studies of Sheard 1978Sheard , 1984, antipsychotic potential (e.g., investigations of Garver Hutchinson 1988;Lenz et al 1987, Lenz et al 1989, antisuicidal and mortality-reducing ability (specifically, studies of Müller-Oerlinghausen et al 1992;Coppen et al 1992), and possibly also antidepressant (Mendels 1976(Mendels , 1982 and antidepressant-augmenting effects (de Montigny et al 1983).…”
mentioning
confidence: 99%
“…The above argument can further be strengthened by looking at lithium as a case in example, and despite its weaker efficacy in preventing recurrent depressive episodes in bipolar patients in comparison to its efficacy in preventing mania, its efficacy in reducing suicide risk in the same patient's group is not contested [7]. Some studies have stipulated that suicide and aggression have an inflammatory origin and that lithium has an anti-inflammatory effects, hence reduces suicide risk as a direct effect [8].…”
Section: To the Editormentioning
confidence: 99%